Tipologi Hukum di Indonesia (Melihat Penggunaan Hukum Prosedural Pada Sistem Peradilan Pidana) - S Sahabuddin (Wajah Hukum, 2018)
Autonomous legal typology which is still very lumpy tasted in order of life laws in Indonesia highlighted on legal activities conducted by the Organization/institution of the law by revealing the face of the legitimate. Pay close attention to the patterns of law enforcement carried out by the institution of law criminal justice system in Indonesia, reflected the application of one law of the intermediate gradations, typology, namely patterns of law enforcement procedural indeed characterizes and autonomous legal power (autonomous law). It is important to note how this autonomous legal typology in its characteristics and how it gives the autonomous law implications against the institution of law criminal justice system in Indonesia in ethos and style of work.